Penatalaksanaa Lansia Wanita Dengan Sindroma Metabolik Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Satelit - Ratu Henggar Audrya Gharrieni; Dian Isti Angraini (CV. Jasa Sukses Abadi, 2025)
Metabolic syndrome is a collection of disorders that include insulin resistance, central obesity, dyslipidemia and high blood pressure. Definitions and criteria for diagnosing metabolic syndrome are constantly changing and are a topic of debate. In general, the prevalence of metabolic syndrome (SM) worldwide ranges from 20-25%, while in Indonesia it is 23.34%, with a higher prevalence in men (26.2%) than women (21.4%). Since hypertension and type 2 diabetes mellitus are chronic diseases and require long-term treatment, family physician services are needed to manage these diseases. The analysis in this study is a case report with primary data obtained from anamnesis and physical examination at the health center, and follow-up examinations during home visits to obtain environmental and social data. Secondary data were obtained from the patient's medical record at the Satellite Health Center. Assessment was carried out based on holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. In this case, diagnosis and treatment have been carried out according to theory and relevant journal references. After the intervention was given, there was an improvement in clinical symptoms and increased understanding of the patient and his family. The diagnosis and management of this patient was carried out holistically, patient centered, family approach, and community oriented. Based on a number of recent theories and studies, there is an increase in knowledge among the patient's family.